"Everybody has something": One teacher's beliefs about musical ability and their connection to teaching practice and classroom culture. (July 2019) - Shouldice, Heather Nelson
The purpose of this case study was to explore one elementary music teacher's beliefs about the nature of musical ability and the ways in which these beliefs relate to actions and lived experiences in the classroom. Data included extensive classroom observations documented through fieldnotes and video footage, semi-structured interviews, teacher journal entries, teaching artifacts, and researcher memos. Three themes emerged from the data: (a) enabling success for all; (b) power of the learning environment; and (c) encouraging lifelong engagement with music. The findings of this study suggest that music educators' beliefs about students' musical abilities relate to their actions in the music classroom, their interactions with students, and their beliefs about the purpose of music education. Music educators should reflect on their beliefs, the ways in which they relate to teaching practice, and the impact they may have on students' musical achievement and musical identity development. Additionally, music teacher educators should consider the role they might play in helping pre-service as well as in-service music teachers examine and possibly reshape their beliefs about music teaching and learning.